ANALISIS KETIMPANGAN DISTRIBUSI PENDAPATAN 33 PROVINSI DI INDONESIA - Chrisamba, Galaxi; Saraswati, Birgitta Dian (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2016)
This study aims to determine the factors that infl uence the unequality distribution of income in Indonesia. This study uses panel data with the time of year during the period 2007-2012 and cross section 33 provinces in Indonesia. Through the fi xed effect estimation model result that infl ation is negative and signifi cant effect on the unequality distribution of income and education while government spending and a signifi cant positive effect on the unequality distribution of income.